Pseudo-positive Information and COVID-19: Reasons behind Sharing Fake News (Georgian Social Media Analysis) - Liana Markariani; Maia Toradze (Athens Journal of Mass Media and Communications)
A plethora of studies state that a perceptible gap can be observed concerning disinformation influence analysis, which is presented by a lack of research on this phenomenon. In a crisis precipitated by the pandemic disruption, the necessity to scrutinize these topics becomes particularly transparent, as an individual’s critical thinking is incapacitated, which leads to a surge in fake news sharing. The article aims to expose and investigate the characteristics of a new, pseudo-positive disposition of false information and the reasons behind its extensive dissemination. By analyzing the original sources of fake news published on "Facebook", conducting an in-depth interview with eight field experts, integrated with a small survey of 204 Georgians, we identify that to overcome the pandemic-induced stress and create an optimistic environment, any positive information that is apprehensible under these conditions becomes effortlessly shareable and consequently, pseudo-positivity is utilized as a manipulator to foment a wave of disinfodemy.